Torsades de Pointes Akibat Bradikardia - Kurniawan, James C.; Setiadi, Benny M.; Rampengan, Starry H. (Medical Scope Journal, 2025)
Abstract: Torsades de pointes (TdP) is a fatal tachyarrhythmia that has the potential to degenerate into ventricular fibrillation. The occurrence of TdP is associated with prolongation of the QT interval on the electrocardiogram (ECG), which is often found in bradycardia patients. We reported an 86-year-old female who experienced recurrent fainting episodes in the past month. From the ECG we recorded sinus rhythm was bradycardia with a heart rate of 43 bpm with a high degree of atrioventricular block, with a prolongation of the QT interval reaching 640 milliseconds. The patient was not taking any medications known to have the effect of prolonging the QT interval. The patient underwent a series of examination. Blood and electrolyte tests were within normal limit. Echocardiography examination showed good heart pump function and no structural abnormalities were found. The 24-hour Holter examination recorded a TdP rhythm with a heart rate of 180 bpm which was spontaneos termination. The patient underwent a permanent dual chamber pacemaker implantation. At post-insertion follow-up, the patient never experienced another fainting episode. In conclusion, bradycardia on ECG is known to prolong the QT interval thereby predisposing to torsades de pointes. Implantation of a permanent pacemaker was done and was successful in treating bradycardia, shortening the QT interval thereby suppressing the occurrence of torsades de pointes. Keywords: torsades de pointes; bradycardia; atrioventricular block    Abstrak: Torsades de pointes (TdP) merupakan takiaritmia fatal yang berpotensi berdegenerasi menjadi fibrilasi ventrikel. Kejadian TdP dikaitkan dengan pemanjangan interval QT pada elektrokardiogram (EKG), yang seringkali dijumpai pada pasien bradikardia. Kami melaporkan kasus seorang pasien wanita berusia 86 tahun yang mengalami episode pingsan berulang dalam satu bulan terakhir. Dari gambaran  EKG didapatkan irama sinus bradikardia dengan laju jantung 43x per menit dengan blok atrioventrikular derajat tinggi, dengan pemanjangan interval QT mencapai 640 milidetik. Pasien tidak mengonsumsi obat-obatan yang diketahui memiliki efek memperpanjang interval QT. Pasien menjalani serangkaian penunjang. Pemeriksaan darah dan elektrolit hasilnya normal. Pemeriksaan ekokardiografi menunjukkan fungsi pompa jantung baik dan tidak ditemukan adanya abnormalitas struktur jantung. Pemeriksaan Holter 24 jam berhasil merekam irama TdP dengan laju jantung 180x per menit yang mengalami terminasi spontan. Pada pasien dilakukan pemasangan alat pacu jantung permanen dual chamber. Pada follow up paska pemasangan, pasien tidak pernah mengalami episode pingsan lagi. Simpulan kasus ini ialah bradikardia pada elektrokardiogram diketahui memperpanjang interval QT sehingga memredisposisi terjadinya TdP. Pemasangan alat pacu jantung permanen pada pasien dipilih sebagai langkah tatalaksana, dan terbukti berhasil mengatasi bradikardia, memperpendek interval QT sehingga mensupresi terjadinya torsades de pointes. Kata kunci: torsades de pointes; bradikardia; blok atrioventrikular